Schumpeter and Marx on Capitalist Transformation - Elliott, John E. (Quarterly Journal of Economics, 1983)
Journal Article Schumpeter and Marx on Capitalist Transformation Get access John E. Elliott John E. Elliott University of Southern California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 98, Issue 2, May 1983, Pages 333–336, https://doi.org/10.2307/1885629 Published: 01 May 1983